2011
DOI: 10.1111/j.1749-6632.2011.06061.x
|View full text |Cite
|
Sign up to set email alerts
|

Barrett's esophagus and animal models

Abstract: Concise summaries Significant progress has been made in the last few decades using animal models to recreate the esophagitis–metaplasia–carcinoma sequence similar to that seen in human Barrett’s esophagus (BE) and EAC. More recent works focus on molecular pathways associated with intestinal metaplasia and carcinogenesis, as well as similarities between genetic mutations occurring in humans and animal models, mouse, rat, pig, rabbit, guinea pig, dog, cat, ferret, and possum. Despite the lack of a perfect mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…5c ). As p63 + KRT7 + cells have been shown to generate intestinal-like epithelial cells in organoid culture upon CDX2 overexpression, it may be possible that these oesophageal cells could be related to the transitional zone progenitor cells previously observed in humans 21 .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…5c ). As p63 + KRT7 + cells have been shown to generate intestinal-like epithelial cells in organoid culture upon CDX2 overexpression, it may be possible that these oesophageal cells could be related to the transitional zone progenitor cells previously observed in humans 21 .…”
Section: Resultsmentioning
confidence: 87%
“…Many of the proposed BO origin theories are based on transgenic mouse studies, and the submucosal gland cell theories are based on human histopathology studies. Unfortunately, submucosal gland theories cannot be tested in mice since mice and humans have key differences in their gastrointestinal anatomy, and rodents lack oesophageal glands 21 . These difficulties argue for an unbiased and systematic genetic approach to BO characterisation in humans with all relevant control cell types to better understand the origin of BO cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Even healthy individuals experience regurgitation of duodenal fluid into the stomach after eating, and the amount regurgitated increases in patients with GERD reportedly. Thus, lying down after eating can result in the duodenal fluid, which contains bile acids, remaining in the stomach (e.g., during sleep) . Suzuki et al .…”
Section: Barrett's Carcinogensismentioning
confidence: 99%
“…Thus, lying down after eating can result in the duodenal fluid, which contains bile acids, remaining in the stomach (e.g., during sleep). 121 Suzuki et al 122 have reported that the cardia has the highest concentration of nitrates originating from food, which maximizes the luminal generation of N-nitroso-compounds from dietary nitrate at the most proximal cardiac region of the acidic stomach. Because the accumulated reflux fluid would contain endogenous N-nitroso-bile acids from the stomach, chronic inflammation and carcinogenesis could then occur in the esophagogastric junction or esophagus.…”
Section: Activation Of Nf-κbmentioning
confidence: 99%
“…Gastric contents are easily pooled, and N -nitroso compounds could be generated at night, in the gastric juice with the refluxate including bile acids in the fornix located on the posterior side of the body. Moreover, both the esophagus and the proximal cardia portion are easily exposed to the N -nitroso compounds by transient lower esophageal sphincter relaxation as well as other lower esophageal sphincter pressure abnormalities in the supine position ( Macke et al, 2011 ). We reported that one of these nitroso compounds, N -nitroso glycocholic, rapidly decomposed under alkaline conditions (pH 9) [t (1/2) = 0.96 h] but remained quite stable under acidic (pH 2) [t (1/2) = 12.8 h] and neutral (pH 7) [t (1/2) = 7.8 h] conditions ( Araki et al, 2008 ).…”
Section: Cardia Adenocarcinoma Associated With Ger Resembling Eacmentioning
confidence: 99%